Analisis Pengaruh Job Demand terhadap Work Engagement melalui Burnout - Barrotul Jazilah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
The aim of this research was to explore burnout, work engagement, and job demand among debt collector workers. The total available population of employees (N= 32) Consumer Collection and Remedial Unit Bank Tabungan Negara Cabang Surabaya participated in this study. Utrecht Work Engagement Scale, Maslach Burnout Inventory and Job demand scale were used as measuring instruments. Partial Least Square (PLS) and supported by SmartPLS 3.0 software were used as a statistical analysis. The result showed that job demand has significant positive effect on work engagement and burnout. On the contrary, burnout has no significant effect on work engagement and cannot mediated the effect of job demand on work engagement. Improved job resources and managing challenge demands are offered as recommendations to improve employee engagement.